Laser-induced actuation of individual microsize liquid metal droplets on an open solid surface. (22nd December 2016) - Liu, Wei; Wang, Chunqing; Dou, Guangbin; Tian, Yanhong; Yang, Lei
Abstract: The actuation of microsize liquid metal droplets on an open solid surface with laser offset heating is reported in this work. The process allows the droplets to move towards the laser beam center. The analysis of the actuations showed that the droplets were predominantly driven by the thermally induced wettability alteration on the solid; in contrast, Marangoni flow and vapor recoil weakened the motion of the droplets. This indicates that a localized thermal gradient was the driving force for droplet motion and suggests that it may be an alternative actuation technique in manipulating liquid metal droplets for microsystems.